2017
DOI: 10.18632/oncotarget.19062
|View full text |Cite
|
Sign up to set email alerts
|

Altered microRNAs expression in T cells of patients with SLE involved in the lack of vitamin D

Abstract: Vitamin D has been recognized as a potent immunomodulator and its deficiency is common in different population groups including patients with SLE. As miRNAs regulation plays a significant role in SLE, the present study aimed to evaluate the association between vitamin D status and miRNAs levels in patients with SLE. The serum concentrations of vitamin D (25-hydroxyvitamin D) and the levels of six miRNAs in T cells from patients with SLE were measured in 42 SLE cases and 48 healthy controls. Vitamin D treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…We confirmed that VDR protein is induced by T cell activation ( Fig. S4a), addition of active VitD enhances VDR expression 27 ( (Fig. S4e).…”
supporting
confidence: 75%
“…We confirmed that VDR protein is induced by T cell activation ( Fig. S4a), addition of active VitD enhances VDR expression 27 ( (Fig. S4e).…”
supporting
confidence: 75%
“…Through vitamin D supplementation for 6 months in patients with SLE ( n = 20), hypovitaminosis D, Treg-cell balance (increased Treg cells and decreased effector Th1 and Th17 cells) and B-cell homeostasis were restored with reduced anti-dsDNA antibodies ( 162 ). Low levels of vitamin D (<20 ng/mL) were associated with reduced micro (mi)-RNA expression in T cells ( i.e ., miRNA-377, miRNA-342, miRNA-10a, miRNA-374b, miRNA-125a, and miRNA-410) of patients with SLE compared with those of healthy controls, indicating that unfavorable immunological alterations take place because of a lack of vitamin D in patients with SLE ( 163 ).…”
Section: Micronutrientsmentioning
confidence: 99%
“…An interesting link between different risk factors was found in a study measuring vitamin D levels in SLE patients and correlating them with certain miRNA levels in patients’ T cells. An association between vitamin D concentrations and measured miRNA levels (miRNA-377, miRNA-342, miRNA-10a, miRNA-374b, miRNA-125a, and miRNA-410) was observed – not only comparing SLE patients with healthy controls, but also between patients differing in their vitamin D serum levels and also in cultured T cells from SLE patients, wherever the correlation was dose-dependent and time-dependent [ 80 ▪▪ ].…”
Section: Another New Participant: Micrornasmentioning
confidence: 99%